Author Correction: Band gap closure, incommensurability and molecular dissociation of dense chlorine - Philip Dalladay-Simpson (Nature Portfolio, 2019)
The original version of this Article omitted references to previous experimental reports on solid hydrogen that are relevant for a full understanding of the context of the previous work. The added references are: 47. Akahama, Y. et al. Evidence from x-ray diffraction of orientational ordering in phase III of solid hydrogen at pressures up to 183 GPa. Phys. Rev. B 82, 060101 (2010). 48. Zha, C.-S., Liu, Z. & Hemley, R. J. Synchrotron infrared measurements of dense hydrogen to 360 GPa. Phys. Rev. Lett. 108, 146402 (2012). 49. Dias, R. & Silvera, I. Observation of the Wigner-Huntington transition to metallic hydrogen. Science 355, 715–718 (2017). 50. Eremets, M. I. & Drozdov, A. P. Comments on the claimed observation of the Wigner-Huntington transition to metallic hydrogen. Preprint at http://arxiv.org/abs/1702.05125 (2017). 51. Loubeyre, P., Occelli, F. & Dumas, P. Comment on: “Observation of the Wigner-Huntington transition to metallic hydrogen”. Preprint at http://arxiv.org/abs/1702.07192 (2017). 52. Goncharov, A. F. & Struzhkin, V. V. Comment on “Observation of the Wigner-Huntington transition to metallic hydrogen”. Science 357, eaam9736 (2017). 53. Liu, X.-D., Dalladay-Simpson, P., Howie, R. T., Li, B. & Gregoryanz, E. Comment on “Observation of the Wigner-Huntington transition to metallic hydrogen”. Science 357, eaan2671 (2017). Citations to these reference, plus reference 21, have been added to the fourth sentence of the Introduction: ‘The experimental realisation of atomic metallic hydrogen has remained elusive despite intense research efforts lasting over 30 years4–7,21,47–53.’ This has been corrected in the PDF and HTML versions of the Article.